Tritrophic associations and identification key for European species of the genus Binodoxys (Mackauer) (Hymenoptera: Braconidae: Aphidiinae) - Lazarević, Maja J.; Žikić, Vladimir A.; Milenković, Darija N.; Tomanović, Željko M. (Archives of Biological Sciences, 2024)
Paper description: The genus Binodoxys, though widely distributed globally, is represented by only nine species in Europe. Through a comprehensive literature review, morphological examination, and molecular analysis, this study elucidates tri-trophic associations and genetic distances. New hosts were identified. Binodoxys similis exhibited a broader geographical distribution. This research provides insights into the biology, morphology, and genetic diversity of European Binodoxys species, and a key for identification. Abstract: The genus Binodoxys includes only nine species found in Europe, yet despite its frequent occurrence, it remains insufficiently studied. This study addresses this knowledge gap through an exhaustive literature review and material collection, and a compilation of a comprehensive list detailing tritrophic associations. Based on the available molecular data, we constructed a maximum likelihood tree and a TSC (‘Statistical Parsimony’) haplotype network for six European species. Several new hosts were identified for the first time, and the geographical distribution of one species was broadened. An identification key for females of European Binodoxys species is provided. Future studies should prioritize gathering host data and investigate the existence of cryptic species among polyphagous species. Furthermore, the status of the three species not analyzed in this study due to the lack of material should be investigated by encompassing both morphological and molecular approaches.